Trophectoderm Biopsy Differentially Influences the Level of Serum β-Human Chorionic Gonadotropin With Different Embryonic Trophectoderm Scores in Early Pregnancy From 7847 Single-Blastocyst Transfer Cycles - Li, Yuan; Wen, Quan; Liao, Jingnan; Ma, Shujuan; Zhang, Shuoping; Gu, Yifan; Tang, Yi; Luo, Keli; Yang, Xiaoyi; Lu, Guang-Xiu; Lin, Ge; Gong, Fei (Frontiers in Endocrinology, 2022)
Objective: To evaluate whether trophectoderm (TE) biopsy differentially influence the level of serum β-human chorionic gonadotropin (β-hCG) with different TE-scored blastocysts transferred in early pregnancy. Methods: This retrospective cohort study contained 7847 single-blastocyst transfer cycles executed between January 2019 and June 2020, including 2657 preimplantation genetic testing (PGT) cycles and 5190 in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) cycles. All cycles were classified into biopsy and control groups, and further stratified based on the TE morphological scores into three subgroups: grades A, B, and C for TE scores, respectively. Intra-group and inter-group analyses were performed on serum β-hCG levels on the 12th day after blastocyst transfer (HCG12), and obstetric and neonatal outcomes. Results: For cycles with a live birth, in grade A TE score subgroups, the HCG12 level did not exhibit statistical significance between the biopsy and control groups (761 mIU/mL vs. 725 mIU/mL, P=0.631). In contrast, in grade B and C TE score subgroups, the control group showed a significantly higher level of HCG12 relative to the biopsy group (663 mIU/mL vs. 624 mIU/mL, P=0.001; 565 mIU/mL vs. 483 mIU/mL, P＜0.001, respectively). We observed no statistically significant differences in obvious adverse obstetric and neonatal outcomes between the same TE-score subgroups of the biopsy group and control group. Conclusions: While blastocysts with higher TE grades produced higher serum β-hCG levels in early pregnancy, TE biopsy might exert a negative impact on serum β-hCG levels by blastocysts with a grade-B TE score and below. TE biopsy did not increase the risk for adverse obstetric and neonatal outcomes.